2015
DOI: 10.1144/sp420.6
|View full text |Cite
|
Sign up to set email alerts
|

A multidisciplinary study of the final episode of the Manda Hararo dyke sequence, Ethiopia, and implications for trends in volcanism during the rifting cycle

Abstract: The sequence of dyke intrusions between 2005 and 2010 in the Manda Hararo rift segment, Ethiopia, provided an opportunity to test conceptual models of continental rifting. Based on trends up to dyke 13 in the sequence, it was anticipated that, should magma supply continue, dykes would shorten in length and eruptions would increase in size and decrease in distance from the segment centre as extensional stress was progressively released. In this paper we revisit these predictions by presenting a comprehensive ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 65 publications
(75 reference statements)
3
61
0
Order By: Relevance
“…Over the next 5 years there were 12 more dykes with an average length of 9.5 km, width of 1.7 m, depth range of 0-10 km and volume of 90 × 10 6 m 3 (Hamling et al, 2009;Ferguson et al, 2010). These were all fed by a magma source below the middle of the rift segment that deflated as rising magma intruded (Grandin et al, 2009 (Ferguson et al, 2010;Barnie et al, 2015). Sulfur dioxide plumes were consistent with volatile loss solely from the extruded volumes of lava.…”
Section: Dabbahu-manda Hararo (2005-2010)mentioning
confidence: 92%
“…Over the next 5 years there were 12 more dykes with an average length of 9.5 km, width of 1.7 m, depth range of 0-10 km and volume of 90 × 10 6 m 3 (Hamling et al, 2009;Ferguson et al, 2010). These were all fed by a magma source below the middle of the rift segment that deflated as rising magma intruded (Grandin et al, 2009 (Ferguson et al, 2010;Barnie et al, 2015). Sulfur dioxide plumes were consistent with volatile loss solely from the extruded volumes of lava.…”
Section: Dabbahu-manda Hararo (2005-2010)mentioning
confidence: 92%
“…At the southern edge of the Danakil depression, there are the Amarta-Barawli volcanic complex (ABVS), Afdera volcano (AV), and Alayta volcano (ALV) (Barberi and Varet, 1970). To the south of the Danakil depression in central west Afar, the rift axis steps en echelon to the southwest into the Dabbahu segment (DVS), which underwent a major dike intrusion episode during (Wright et al, 2006Ebinger et al, 2008;Barnie et al, 2015). Nabro volcano (NVS), which erupted in June 2011, is on the eastern margin of the Danakil depression near the Eritrean-Ethiopian border (Hamlyn et al, 2014;Goitom et al, 2015;Fig.…”
Section: Geological Settingmentioning
confidence: 99%
“…Over the next five years, 13 smaller dykes intruded a further c. 1 km 3 of magma (Hamling et al , 2010Grandin et al 2010b;Belachew et al 2011;Barnie et al 2015) and there were three further eruptions (Ferguson et al 2010;Barnie et al 2015). These were also fed from the Ado 'Ale Volcanic Complex at the centre of the rift Belachew et al 2011;Grandin et al 2011).…”
Section: The Dabbahu Rifting Episode and The Afar Rift Consortiummentioning
confidence: 99%
“…The investigations have been wide in scope and have included the production of a new geological map of the Dabbahu (Manda -Hararo) spreading centre (Vye-Brown et al 2016a). Detailed forensic investigations have revealed the details of dyke intrusions and eruptions using data from local seismic arrays Grandin et al 2011), satellite geodesy Grandin et al 2010b), geology/petrology (Ferguson et al 2010) and combinations of these techniques Barnie et al 2015). These studies have shown that dykes can interact in space and time, possibly through stress interactions (Hamling et al 2010), and that the style of volcanism and intrusion is highly variable in space (Pagli et al 2012).…”
Section: The Dabbahu Rifting Episode and The Afar Rift Consortiummentioning
confidence: 99%